PENERAPAN MODEL PEMBELAJARAN COOPERATIVE TIPE TALKING STICK TERHADAP HASIL BELAJAR SISWA X IPS DI SMA NEGERI 2 MANIAMOLO - Sopardin Zebua (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
The aim of this research is to determine the improvement in student learning outcomes through the application of the Talking Stick Type Cooperative learning model to student learning outcomes. The subjects of this research were 26 class X IPS students. The results of this research obtained an average initial test score of 64.96%, an average final test score of 82.08%. Conclusions, namely: (1) The Talking Stick Type Cooperative Learning Model can improve student learning outcomes, this is because by implementing the Talking Stick Type Cooperative Learning Model students are more active in learning activities and can understand the concept of the material well, (2) Student learning outcomes increased from 64.96% in the first cycle, it turns out that the percentage of student learning completion has not met the target set at 75%. So it was continued in the second cycle with 82.08%, with a very good category because these results showed very good results. Based on the level of student learning success, in this case the target of success has been achieved. Suggestions, namely: (1) The application of the Talking Stick Type Cooperative learning model provides better learning outcomes compared to conventional learning models, so it is hoped that schools, especially teachers, can apply the Talking Stick Type Cooperative learning model to other materials that are appropriate to this learning. , (2) For researchers who will use the Talking Stick Type Cooperative learning model, they should be able to collaborate well with observers so that they can improve the learning process to get optimal results, (3) The teacher should always encourage students to be more active so that the teacher only acts as facilitator for students.